Continuous production method of metal graphene composite material

Through a continuous production method, the combination of NaCl, KCl and boron carbide and metal is solved by solving the problems of discontinuity, complexity and high cost of the existing metal graphene composite production methods, and the efficient and stable production of metal graphene composite materials is achieved.

CN119753413AActive Publication Date: 2025-04-04CHAOWEI POWER GROUP CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411962258.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-04
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing metal graphene composite production methods have problems such as inability to produce continuously, complex processes, inability to meet industrial production, and high production costs.

Method used

The process is repeated to achieve continuous production of metal graphene composite materials by mixing, melting, cooling, crushing, and adding boron carbide to form a precursor slag, which is then melted and poured with the metal in a heating stirring device.

Benefits of technology

Continuous production of metal graphene composite materials is realized, production costs are reduced, process is simplified, production efficiency is improved, and the performance of graphene content, size and number of layers is stable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753413A_ABST
    Figure CN119753413A_ABST
Patent Text Reader

Abstract

The invention relates to a continuous production method of a metal graphene composite material, belongs to the technical field of graphene composite materials, and is used for solving at least one of the problems of incapability of continuous production, complex process, incapability of meeting industrial production, high production cost and the like in the existing method. According to the method, the matrix metal and the precursor slag with the precursor are added after each time of casting, at least 20 times of circulation production is achieved, and the method has the advantages of being energy-saving, easy to operate, stable in process, high in production efficiency and the like. And the metal graphene composite material prepared by the method is stable in graphene content, size, layer number and other properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of graphene composite materials, and in particular to a method for continuously producing a metal graphene composite material. Background Art

[0002] Graphene is one of the strongest materials known. It also has good toughness and can be bent. The theoretical Young's modulus of graphene is 1.0 TPa and the inherent tensile strength is 130 GPa. The carrier mobility of graphene at room temperature is about 15000 cm 2 / (V·s), which is more than 10 times that of silicon and more than twice that of indium antimonide (InSb), the material with the highest known carrier mobility. Under certain specific conditions, such as low temperature, the carrier mobility of graphene can even reach 250,000 cm 2 / (V·s). Unlike many materials, the electron mobility of graphene is less affected by temperature changes. At any temperature between 50 and 500K, the electron mobility of a single layer of graphene is 15000cm 2 / (V·s) approximately.

[0003] Due to the many excellent properties of graphene itself, it is used in more and more fields. In recent years, with the rapid development of new energy and energy storage fields, the application of graphene in the battery field has become more and more common. For example, it is directly added to the active material as a battery additive to improve the porosity of the active material, enhance the conductivity and charging acceptance of the active material, and improve the battery's anti-sulfurization performance and deep cycle performance. Adding graphene to the grid alloy to prepare graphene alloy can combine the conductivity and mechanical properties of the alloy, effectively solve the problem of interface bonding between the active material and the grid, and avoid premature capacity loss. At the same time, it can greatly improve the corrosion resistance and creep resistance of the grid, effectively extending the service life of the battery. Because of the excellent properties of graphene alloys, graphene alloys have been widely used in the battery energy field.

[0004] Currently, metal graphene is receiving more and more attention in the field of material applications and has been widely used. By adding graphene materials to metal materials, the hardness, conductivity, corrosion resistance and other factors that are beneficial to improving product performance can be changed.

[0005] However, metal graphene composite materials currently have problems such as the inability to produce continuously, complex processes, inability to meet industrial production requirements, and high production costs. Summary of the invention

[0006] In view of the above analysis, the present invention aims to provide a method for continuous production of metal graphene composite materials to solve at least one of the problems of existing methods, such as inability to produce continuously, complex processes, inability to meet industrial production requirements, and high production costs.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] A method for continuously producing a metal-graphene composite material comprises the following steps:

[0009] (1) NaCl and KCl are mixed, melted, cooled, crushed, boron carbide is added, and mixed evenly to obtain a precursor slag;

[0010] (2) adding a certain amount of metal and a certain amount of the precursor slag described in step (1) into a heating and stirring device with a discharge function at the bottom, melting and heat-insulating;

[0011] (3) discharging a certain amount of melt at the bottom of the heating and stirring device, and pouring the melt into a mold to obtain a metal graphene composite ingot;

[0012] (4) adding a metal having the same mass as the melt discharged in step (3) and a certain amount of the precursor slag obtained in step (1) into the heating and stirring device, melting and heat-insulating the metal;

[0013] (5) Repeat steps (3) and (4) to achieve continuous production of metal graphene composite materials.

[0014] Furthermore, in step (1), the molar ratio of NaCl to KCl is 2:3 to 2:1, preferably, 2:3 to 3:2.

[0015] Furthermore, in step (1), the melting temperature is 800-900°C, and the melting and dehydration time is 30-60 minutes.

[0016] Furthermore, in step (1), the mass of boron carbide is 4-10% of the total mass of NaCl and KCl, preferably, 5-10%.

[0017] Furthermore, in step (2), the mass ratio of the metal to the precursor slag is 1:0.3-0.5, preferably, 1:0.3-0.4.

[0018] Furthermore, in step (2), the melting temperature is 700-800° C. and the melting time is 0.5-2 h.

[0019] Furthermore, in step (3), the mass ratio of the melt to the metal in step (2) is 0.5 to 0.9:1, preferably 0.8 to 0.9:1.

[0020] Furthermore, in step (3), the mold needs to be preheated at a temperature of 150 to 300° C. for 1 to 2 hours.

[0021] Furthermore, in step (4), the mass ratio of the metal to the precursor slag is 35 to 48:1, preferably 35 to 45:1.

[0022] Furthermore, in step (5), steps (3) and (4) are repeated 4 to 20 times.

[0023] Furthermore, the metal is at least one of lead, aluminum or zinc.

[0024] In a second aspect, the present invention provides a metal graphene composite material prepared by the above method.

[0025] In a third aspect, the present invention provides an application of the above-mentioned metal graphene composite material in battery materials.

[0026] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0027] (1) The method of the present invention melts NaCl and KCl, cools them, and adds boron carbide, so that the salt can be fully dehydrated, the melting point of the melted mixed salt is reduced, and the temperature required for the secondary melting is lower, which is more conducive to the reaction and further increases the content of graphene in the composite material; it is also conducive to reducing the size and number of graphene layers, thereby improving the purity of the composite material;

[0028] (2) The method of the present invention adds base metal and precursor slag with precursor after each casting to achieve at least 20 cycles of production. The method of the present invention has the advantages of energy saving, simple operation, stable process, high production efficiency, etc. The metal graphene composite material prepared by the method of the present invention has stable properties such as graphene content, size, and number of layers, wherein the graphene content is 0.005-0.01%, the graphene size is about (5-20)×(20-40)μm, and the number of layers is 2-3.

[0029] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0031] Figure 1 It is a pouring induction furnace with a teapot spout of the present invention;

[0032] Figure 2 An induction furnace with a plug valve structure according to the present invention;

[0033] Figure 3 An induction furnace of a specific slider valve structure of the present invention;

[0034] Figure 4 An induction furnace of the present invention having a sliding block valve structure with a furnace reactor rotation;

[0035] Figure 5 An induction furnace with a metal pump discharge according to the present invention;

[0036] Figure 6 This is a Raman spectrum of the composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0037] The preferred embodiments of the present invention will be described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0038] A specific embodiment of the present invention discloses a method for continuous production of a metal graphene composite material, comprising the following steps:

[0039] (1) NaCl and KCl are mixed, melted, cooled, crushed, boron carbide is added, and mixed evenly to obtain a precursor slag;

[0040] (2) adding a certain amount of metal and a certain amount of the precursor slag described in step (1) into a heating and stirring device with a discharge function at the bottom, melting and heat-insulating;

[0041] (3) discharging a certain amount of melt at the bottom of the heating and stirring device, and pouring the melt into a mold to obtain a metal graphene composite ingot;

[0042] (4) adding a metal having the same mass as the melt discharged in step (3) and a certain amount of the precursor slag obtained in step (1) into the heating and stirring device, melting and heat-insulating the metal;

[0043] (5) Repeat steps (3) and (4) to achieve continuous production of metal graphene composite materials.

[0044] According to the method of the present invention, NaCl and KCl are melted, cooled, and boron carbide is added, so that the salt can be fully dehydrated, the melting point of the melted mixed salt is reduced, and the temperature required for secondary melting is lower, which is more conducive to the reaction, and the content of graphene in the composite material is further increased; at the same time, it is also conducive to reducing the size and number of layers of graphene, and improving the purity of the composite material.

[0045] The method of the present invention adds base metal and precursor slag with precursor after each casting to achieve at least 20 cycles of production. The method of the present invention has the advantages of energy saving, simple operation, stable process, high production efficiency, etc. The metal graphene composite material prepared by the method of the present invention has stable properties such as graphene content, size, and number of layers. Among them, the graphene content is 0.005-0.01%, the graphene size is about (5-20)×(20-40)μm, and the number of layers is 2-3. It should be noted that the purity of lead in the present invention is 99.99%, the purity of NaCl is 99.8%, and the purity of KCl is 99.8%; the carbon-containing precursor boron carbide (B 4 C) has a mass fraction of boron carbide of ≥96.0% and a particle size of at least F220.

[0046] The carbon source in the method of the present invention comes from boron carbide. Boron carbide decomposes under specific conditions to form carbon atoms, which enter into the lead liquid and reorganize to form a graphene structure after reaching a certain concentration. Therefore, the composite material prepared by the method of the present invention has better bonding between graphene and lead and more uniform dispersion. Secondly, graphene is expensive. Compared with the method of directly adding graphene, the method of the present invention has a cost advantage.

[0047] Preferably, the heating and stirring device described in the present invention is an induction furnace, and the induction furnaces with a discharge function at the bottom of the present invention are all existing structures, for example, Figure 1 The teapot spout is used for pouring, and the melt at the bottom is discharged through the teapot spout; Figure 2 The plug valve structure can discharge the melt from the bottom by removing the plug; Figure 3 The slider valve structure allows the melt to be pumped out from the bottom by opening the valve; Figure 4 The slider valve structure with furnace reactor rotation, the entire furnace can rotate, the discharge port is located at the upper part of the furnace body, the normal liquid is below the discharge port, when the furnace rotates to a certain position, the liquid flows to the discharge port position, and then the valve is opened to discharge the liquid; Figure 5 The metal pump is discharged. The metal pump is arranged on the upper part of the furnace body and pumps out the melt at the bottom through the pipe.

[0048] In a specific embodiment, the molar ratio of NaCl to KCl in step (1) is 2:3 to 2:1, preferably, 2:3 to 3:2, for example, 2:3, 5:6, 1:1, 7:6, 4:3, 3:2.

[0049] The purpose of using NaCl and KCl as the mixed salt in the present invention is that the mixed salt has a lower melting point than a single salt. Within the above-mentioned molar ratio range, the melting point is relatively low near the eutectic point of NaCl and KCl.

[0050] In a specific embodiment, in step (1), the melting temperature is 800-900°C, for example, 800°C, 810°C, 820°C, 830°C, 840°C, 850°C, 860°C, 870°C, 880°C, 890°C, 900°C, and the melting and dehydration time is 30-60 min, for example, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min.

[0051] Within the above melting temperature and time, NaCl and KCl can be fully melted with low energy consumption and will not affect the service life of the equipment.

[0052] In a specific embodiment, in step (1), the powder is crushed to a particle size of less than 3 mm, which is conducive to uniform mixing with boron carbide.

[0053] In a specific embodiment, in step (1), the mass of boron carbide is 4-10% of the total mass of NaCl and KCl, preferably, 5-10%, for example, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%. Since boron carbide is a carbon source, it must be excessive to ensure sufficient graphene content in the product.

[0054] In a specific embodiment, in step (2), the mass ratio of metal to precursor slag is 1:0.3-0.5, preferably, 1:0.3-0.4, for example, 1:0.31, 1:0.32, 1:0.33, 1:0.34, 1:0.35, 1:0.36, 1:0.37, 1:0.38, 1:0.39, 1:0.4. Since the amount of precursor slag is responsible for providing a carbon source, too little amount will affect the final content of the product graphene, or it will take longer to reach the target content; too much amount will be excessive, resulting in unnecessary waste of resources.

[0055] In a specific embodiment, in step (2), the melting temperature is 700-800°C, for example, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, and the time is 0.5-2h, for example, 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h.

[0056] When the temperature is lower than the above range, it is not conducive to the reaction. When the temperature is higher than 800°C, the salt volatilization loss will increase, and the energy consumption will also increase. The time is related to the graphene content. The longer the time, the higher the content.

[0057] In a specific embodiment, in step (3), the mass ratio of the melt to the metal in step (2) is 0.5-0.9:1, preferably 0.8-0.9:1, for example, 0.8:1, 0.81:1, 0.82:1, 0.83:1, 0.84:1, 0.85:1, 0.86:1, 0.87:1, 0.88:1, 0.89:1, 0.9:1. The melt discharged from the bottom is a metal-graphene composite material, and the total amount of the product is approximately equal to the amount of metal. In order to ensure that the salt does not leak out, a small amount of metal should remain at the bottom, and it is safer to leave 10-20%, so 80-90% is discharged.

[0058] In a specific embodiment, in step (3), the mold needs to be preheated at a temperature of 150-300°C (for example, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C) for 1-2h (for example, 1h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h).

[0059] If the mold temperature is too low, the metal will cool too quickly, resulting in large shrinkage holes and affecting subsequent use; if the mold temperature is too high, the metal will cool too slowly, causing component segregation.

[0060] In a specific embodiment, in step (4), the mass ratio of metal to precursor slag is 35 to 48:1, preferably 35 to 45:1, for example, 35:1, 36:1, 37:1, 38:1, 39:1, 40:1, 41:1, 42:1, 43:1, 44:1, 45:1, 46:1, 47:1, 48:1.

[0061] In a specific embodiment, in step (4), the melting temperature is 700-800°C, for example, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, for example, 0.5h, 0.6h, 0.7h, 0.8h, 0.9h, 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h, 2h.

[0062] When the temperature is lower than 700℃, it is not conducive to the reaction. When the temperature is higher than 800℃, it will increase the salt volatilization loss and also increase the energy consumption.

[0063] In a specific embodiment, in step (5), steps (3) and (4) are repeated ≤ 20 times, preferably 4 to 20 times.

[0064] The method of the present invention adds precursor slag after each casting. Due to the increase in carbon ion concentration in the precursor slag, the maximum concentration of graphene in the composite material is achieved in the fourth cycle. After 20 cycles, due to the accumulation of boron carbide decomposition products in the furnace, the graphene content in the composite material begins to decrease. Therefore, 4 to 20 cycles in the present invention are optimal, and the graphene content is relatively high.

[0065] The present invention is made in an induction furnace, in which the convection of the molten metal is ensured due to the electric force, and the mixing of the molten metal is achieved. Molten salt is not conductive, so it can only heat the molten metal and will not move under the action of electromagnetic force. The convection in the molten salt is essentially just a heat flow. The salt heated by the metal rises from the molten metal-salt interface to the salt-furnace atmosphere interface and is replaced by the cooler salt, which ensures the continuous movement of the molten metal-salt interface. This is because boron carbide and salt are mixed together, and the salt at the metal-salt interface moves upward under the action of the heat flow, and the cooler salt at the top sinks, and the boron carbide also accompanies the same movement. The material at the metal-salt interface is constantly changing, thereby playing a stirring role, and no additional mechanical stirring is required.

[0066] In a specific embodiment, the metal is at least one of lead, aluminum or zinc.

[0067] Another specific embodiment of the present invention discloses a metal graphene composite material prepared by the above method.

[0068] Another specific embodiment of the present invention discloses the application of the above-mentioned metal graphene composite material in battery materials.

[0069] The technical solution of the present invention is further explained below in conjunction with specific embodiments.

[0070] It should be noted that in the following examples, the purity of lead is 99.9%, the purity of NaCl is 99.8%, and the purity of KCl is 99.8%; the mass fraction of boron carbide in boron carbide is ≥96.0% and the particle size is F220.

[0071] Example 1

[0072] A method for continuously producing a metal-graphene composite material comprises the following steps:

[0073] (1) NaCl and KCl are mixed in a molar ratio of 1:1, melted and dehydrated at 900° C. for 40 min, cooled, the slag is ground in a porcelain mortar, boron carbide is added, the mass of boron carbide is 5% of the total mass of NaCl and KCl, and mixed evenly to obtain a precursor slag;

[0074] (2) adding lead and the precursor slag into an induction furnace with a discharge function at the bottom, wherein the mass ratio of lead to the precursor slag is 1:0.3, melting at 800° C. and keeping the temperature for 1 hour;

[0075] (3) discharging a certain amount of melt at the bottom of the induction furnace, wherein the mass ratio of the melt to the lead in step (2) is 0.8:1, pouring the melt into a metal mold, and preheating the metal mold at 290° C. for 1 h to obtain a metal-graphene composite ingot;

[0076] (4) adding lead of the same mass as the melt discharged in step (3) and a certain amount of the precursor slag obtained in step (1) into the induction furnace, wherein the mass ratio of lead to precursor slag is 35:1, melting at 800° C. and keeping the temperature for 1 hour;

[0077] (5) Repeat steps (3) and (4) 20 times to achieve continuous production of metal graphene composite materials.

[0078] Example 2

[0079] A method for continuously producing a metal-graphene composite material comprises the following steps:

[0080] (1) NaCl and KCl are mixed in a molar ratio of 2:3, melted and dehydrated at 800° C. for 60 min, cooled, the slag is ground in a porcelain mortar, boron carbide is added, the mass of boron carbide is 7.5% of the total mass of NaCl and KCl, and mixed evenly to obtain a precursor slag;

[0081] (2) adding lead and the precursor slag into an induction furnace with a discharge function at the bottom, wherein the mass ratio of lead to the precursor slag is 1:0.35, melting at 750° C. and keeping the temperature for 1.25 h;

[0082] (3) discharging a certain amount of melt at the bottom of the induction furnace, wherein the mass ratio of the melt to the lead in step (2) is 0.85:1, pouring the melt into a metal mold, and preheating the metal mold at 150° C. for 2 h to obtain a metal graphene composite ingot;

[0083] (4) adding lead of the same mass as the melt discharged in step (3) and a certain amount of the precursor slag obtained in step (1) into the induction furnace, wherein the mass ratio of lead to precursor slag is 40:1, melting at 750° C. and keeping the temperature for 1.25 h;

[0084] (5) Repeat steps (3) and (4) 20 times to achieve continuous production of metal graphene composite materials.

[0085] Example 3

[0086] A method for continuously producing a metal-graphene composite material comprises the following steps:

[0087] (1) NaCl and KCl are mixed in a molar ratio of 3:2, melted and dehydrated at 850° C. for 30 min, cooled, the slag is ground in a porcelain mortar, boron carbide is added, the mass of boron carbide is 10% of the total mass of NaCl and KCl, and mixed evenly to obtain a precursor slag;

[0088] (2) adding lead and the precursor slag into an induction furnace with a discharge function at the bottom, wherein the mass ratio of lead to the precursor slag is 1:0.4, melting at 700° C. and keeping the temperature for 2 hours;

[0089] (3) discharging a certain amount of melt at the bottom of the induction furnace, wherein the mass ratio of the melt to the lead in step (2) is 0.9:1, pouring the melt into a metal mold, and preheating the metal mold at 230° C. for 1.5 h to obtain a metal graphene composite ingot;

[0090] (4) adding lead of the same mass as the melt discharged in step (3) and a certain amount of the precursor slag obtained in step (1) into the induction furnace, wherein the mass ratio of lead to precursor slag is 45:1, melting at 700° C. and keeping the temperature for 2 h;

[0091] (5) Repeat steps (3) and (4) 20 times to achieve continuous production of metal graphene composite materials.

[0092] Example 4

[0093] The method for preparing a metal graphene composite material in this embodiment is the same as that in Embodiment 1, except that in step (1), the molar ratio of NaCl to KCl is 2:1.

[0094] Example 5

[0095] The preparation method of a metal graphene composite material in this embodiment is the same as that in Embodiment 1, except that in step (1), the mass of boron carbide is 4% of the total mass of NaCl and KCl.

[0096] Example 6

[0097] The method for preparing a metal graphene composite material in this embodiment is the same as that in Embodiment 1, except that in step (2), the mass ratio of lead to precursor slag is 1:0.5.

[0098] Example 7

[0099] The preparation method of a metal graphene composite material in this comparative example is the same as that in Example 1, except that in step (3), the mass ratio of the melt to the lead in step (2) is 0.5:1.

[0100] Example 8

[0101] The preparation method of a metal graphene composite material in this comparative example is the same as that in Example 1, except that in step (4), the mass ratio of lead to precursor slag is 48:1.

[0102] Comparative Example 1

[0103] The preparation method of a metal graphene composite material in this comparative example is the same as that in Example 1, except that in step (1), KCl, NaCl and boron carbide are directly mixed without melting, cooling and pulverizing KCl and NaCl.

[0104] Test Example 1

[0105] The metal graphene composite ingots prepared by cycles 1 to 20 times in Examples 1-8 and Comparative Example 1 were respectively taken, and the carbon content was checked on a Leco C744-MHC carbon analyzer, and the carbon modification was checked on a Renishaw INVIA0820-04 confocal Raman scattering spectrometer. The results are shown in Table 1.

[0106] The Raman spectrum of the composite material prepared in Example 1 is as follows: Figure 6 As shown, the intensity ratio of the 2D and G peaks I2D / IG is equal to 0.61, which indicates that two layers of graphene are formed. The number of graphene layers of the products obtained in other embodiments or comparative examples are also tested using the same method.

[0107] Table 1

[0108]

[0109]

[0110] From Examples 1-3, the carbon content is higher when the cycle is 4 to 20 times. This is because the carbon ion concentration in the precursor slag increases. The maximum concentration of graphene in the composite material is achieved in the 4th cycle. After 20 cycles, the graphene content in the composite material begins to decrease due to the accumulation of boron carbide decomposition products in the furnace. Therefore, 4 to 20 cycles in the present invention are optimal and the graphene content is higher.

[0111] Compared with Example 1, the graphene content in the prepared composite materials of Example 4-5 is significantly reduced.

[0112] Compared with Example 1, Examples 6-7 increase the input of raw materials and reduce the output of composite materials. Although the graphene content in the composite materials is similar to that in Example 1, the production cost is increased and the production efficiency is reduced. Secondly, the number of graphene layers in Example 6 is also slightly increased.

[0113] Compared with Example 1, Example 8 reduces the input of carbon-containing agent during continuous production. The graphene content in the composite material produced in the first few cycles is similar to that in Example 1. Later, due to the reduction of carbon source, the graphene content shows a downward trend.

[0114] Compared with Example 1, Comparative Example 1 eliminates the raw material pretreatment step, the graphene content in the composite material is significantly reduced, and the number of graphene layers is increased.

[0115] Test Example 2

[0116] The metal graphene composite ingots prepared in Examples 1-8 and Comparative Example 1-cycle 10 were respectively taken for corrosion weight loss test. The corrosion weight loss of each material is shown in Table 2.

[0117] Corrosion weight loss test process: ambient temperature 25°C, current density 43mA / cm 2 , the corrosive medium has a density of 1.28g / cm 3 After the test, the surface corrosion layer was washed off with a sugar-alkali solution, and the weight changes before and after corrosion were compared.

[0118] Table 2

[0119]

[0120]

[0121] Compared with Example 1, the corrosion weight loss of the composite materials in Example 4-5 was significantly increased, and the corrosion resistance of the prepared composite materials was reduced.

[0122] Compared with Example 1, the corrosion weight loss of the composite materials in Examples 6-7 is similar, indicating that the corrosion resistance of the materials is similar, but Example 6 increases the production cost and Example 7 reduces the production efficiency.

[0123] Compared with Example 1, the corrosion weight loss of the composite material in Example 8 is slightly increased, and the corrosion resistance of the prepared composite material is reduced.

[0124] Compared with Example 1, the corrosion weight loss of the composite material in Comparative Example 1 is significantly increased, indicating that the corrosion resistance of the composite material prepared without the raw material pretreatment process of the present invention is reduced.

[0125] The lead-graphene composite material prepared by the method of the present invention has a high content of graphene and is evenly dispersed, which greatly improves the corrosion resistance of the lead material. The method of the present invention realizes the continuous production of the lead-graphene composite material, with stable quality between batches, realizes the reuse of part of the raw materials, reduces the production cost, and improves the production efficiency.

[0126] The inventors have also conducted the above tests on other embodiments, and the results are basically the same. Due to limited space, they are not listed one by one.

[0127] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A method for continuous production of a metal graphene composite material, characterized in that: The steps include: (1) NaCl and KCl are mixed, melted, cooled, crushed, boron carbide is added, and mixed evenly to obtain a precursor slag; (2) adding the metal and the precursor slag described in step (1) into a heating and stirring device with a discharge function at the bottom, melting and heat-insulating; (3) discharging the melt at the bottom of the heating and stirring device, and pouring the melt into a mold to obtain a metal graphene composite ingot; (4) adding metal of the same mass as the melt discharged in step (3) and the precursor slag obtained in step (1) into the heating and stirring device, melting and heat-insulating the metal; (5) Repeat steps (3) and (4) to achieve continuous production of metal graphene composite materials.

2. A method for continuous production of a metal graphene composite material according to claim 1, characterized in that: The molar ratio of NaCl to KCl in step (1) is 2:3 to 2:

1.

3. The method for continuous production of a metal-graphene composite material according to claim 1, characterized in that: In step (1), the melting temperature is 800-900°C, and the melting and dehydration time is 30-60 minutes.

4. A method for continuous production of a metal-graphene composite material according to any one of claims 1 to 3, characterized in that: In step (1), the mass of boron carbide is 4-10% of the total mass of NaCl and KCl.

5. A method for continuous production of a metal-graphene composite material according to any one of claims 1 to 3, characterized in that: In step (2), the mass ratio of metal to precursor slag is 1:0.3-0.5; The melting temperature is 700-800°C and the melting time is 0.5-2h.

6. The method for continuous production of a metal-graphene composite material according to claim 1, characterized in that: In step (3), the mass ratio of the melt to the metal in step (2) is 0.5 to 0.9:1; The mold needs to be preheated at a temperature of 150 to 300° C. for 1 to 2 hours.

7. The method for continuous production of a metal-graphene composite material according to claim 1, characterized in that: In step (4), the mass ratio of metal to precursor slag is 35 to 48:

1.

8. The method for continuous production of a metal-graphene composite material according to any one of claims 1 to 8, characterized in that: The metal is at least one of lead, aluminum or zinc.

9. A metal-graphene composite material prepared by the method according to any one of claims 1 to 8.

10. Use of the metal graphene composite material according to claim 9 in battery materials.

Citation Information

Patent Citations

  • Method for preparing graphene compounds and graphene oxide compounds with high efficiency

    CN101857221A

  • Continuous extrusion preparation method of graphene aluminum alloy conductor

    CN108326311A

  • Polyethylene-graphene composite material and preparation method thereof

    CN112831108A

  • Positive grid alloy containing graphene and preparation method and application thereof

    CN113579210A

  • Graphene oxide fine aggregate in cement composites

    WO2022221754A1